Persepsi tentang NAPZA dalam Penyalahgunaan NAPZA pada Mahasiswa Kota Semarang - Adelia Ismarizha (Jurnal Kesehatan Masyarakat (Undip), 2015)
Drug abuse has become a crucial problem. The number of drug abuse cases is increasing every year in each category of age. Teenagers, in this case, students of high schools and universities are categorized in vulnerable age upon drug abuse. Drug abuse in teenagers is considered as life style. This study is subjected to university students in Semarang since their activities and social environment are more open than high school students. The purpose of this study is to describe the perception of NAPZA upon students’ drug abuse in Semarang. This study was conducted among students in three universities in Semarang due to their different characteristics. This study uses quantitative analytical method with cross sectional approach. 100 respondents were collected as samples using proportional random sampling. The data was analyzed using univariate and bivariate data analysis with Chi Square test. The results showed that the bivariate results were the variable of experience and knowledge, the perception of vulnerability, seriousness, and benefit, while the perception of obstruction had no relationship with students’ drug abuse. The variable of cues to action had significant relationship with students’ drug abuse. The discussion explained the demographic variable of 18-20 years respondents (66%), gender respondents (56%), female with adequate pocket money respondents (≤ Rp. 900,000,-) (58%), experience (51%) was in good category, knowledge (60%) was in poor category, the perception of vulnerability (56%) was not in vulnerable category, the perception of seriousness category (53%) was not in serious state, the perception of benefit (69%) was in beneficial categories, perceptions of obstruction (95%) did not become obstruction, cues to action (63%) was poor and drug abuse (51%) was in lower risk. Suggestion that may be given by the author to universies and Agent of Narcotics Central Java Province (BNP Jawa Tengah) is that fix and open regulations are needed to create drug-free universities as well as governmental integration with preventive and curative programs of drug abuse, especially for teenagers.